Effects of thermomechanical and thermocycling on the shear bond strength of brackets to bovine enamel bonded with conventional and self-etching adhesive systems - Torres, Luciana Sarmento; Alves, Levy Anderson César; Fava, Marcelo; Di Nicoló, Rebeca (Brazilian Dental Science, 2015)
Several adhesive systems have been developed in the last decade. The aim of the current study was to evaluate the shear bond strength of orthodontic brackets bonded with conventional primers or self-etching primers, artificially aged by means of thermocycling and thermomechanical procedures.90 bovine incisors were used in the investigation. The roots were sectioned in the amelo-cementary junction. All samples were randomly divided in 2 groups ( n= 45), according to the primer used for bracket bonding. XT Group–hydrophobic conventional primer (Transbond XT, 3M unitek, Monrovia, Calif); SEP Group –self-etching primer (Transbond Plus SEP, 3 M Unitek, Monrovia, Calif). All specimens were bonded with XT Transbond resin adhesive (3 M Unitek, Monrovia, Calif). A Universal Testing Machine EMIC DL2000 (EMIC Equip. Sist. Ensaio Ltda., São José dos Pinhais, PR, Brazil) was used for the collection of the values of SBS resistance. The results of the current study were: (Prompt L-Pop 1.72±0.13 MPa; Clearfil SE Bond 1.75±0.19 MPa; FL Bond 1.71±0.22 MPa; One-Up Bond 1.77±0.14 MPa; XT Control 10.5±0.86 MPa). In conclusion: the number of cycles in thermal and thermo mechanical cycling did not influence shear bond strength values for any of the primers tested;SEP Transbond Plus showed the greatest values for bond strength of orthodontic brackets.